Siklus Kinerja Guru Berbasis Sasaran Kerja - Aziz Luki Ahyar (Bidayatuna, 2018)
This research aims to determine teacher performance management as a continuous performance process to equalize the individual goals of teachers, educational institutions and concatenation of teacher performance from the planning, implementation, and evaluation stages oriented to meeting minimum work standards in order to obtain income eligibility, allowances, and promotion or rank only resulting in teacher performance dealing with administrative matters and overriding performance processes that produce outputs and outcames according to the goals of educational institutions. This research is a qualitative study with a phenomological approach. The data collection technique uses observation, interviews and documentation. Data analysis includes single site analysis and cross site analysis with data analysis techniques; data reduction, data presentation, and conclusions. This research resulted in four main findings. First, the pre-cycle stage with preparation for assessment and forming a teacher performance appraisal team. Second, the planning stage with a phase of defining, discussing roles, responsibilities, and measurable expectations. Third, the coaching stage with a phase of observation, monitoring, support, feedback, and appreciation. The four stages of the teacher performance management cycle are performance evaluation.